2022
DOI: 10.3390/ijms232314686
|View full text |Cite
|
Sign up to set email alerts
|

First Insights into the Venom Composition of Two Ecuadorian Coral Snakes

Abstract: Micrurus is a medically relevant genus of venomous snakes composed of 85 species. Bites caused by coral snakes are rare, but they are usually associated with very severe and life-threatening clinical manifestations. Ecuador is a highly biodiverse country with a complex natural environment, which is home to approximately 20% of identified Micrurus species. Additionally, it is on the list of Latin American countries with the highest number of snakebites. However, there is no local antivenom available against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…The venom of a subpopulation of M. helleri, which is a taxonomically controversial species, was also characterized. Our samples of M. helleri, M. medemi, and M. sangilensis comprised several members of the PLA 2 and 3FTx families, which is consistent with the results of studies of other South American coral snake venoms [16,17,28,[35][36][37][40][41][42], according to electrophoretic, chromatographic, and proteomic analysis. The properties of Micrurus venoms vary greatly among species, which is attributed to their diverse habitats and prey preferences as well as phylogenetic inertia [12,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The venom of a subpopulation of M. helleri, which is a taxonomically controversial species, was also characterized. Our samples of M. helleri, M. medemi, and M. sangilensis comprised several members of the PLA 2 and 3FTx families, which is consistent with the results of studies of other South American coral snake venoms [16,17,28,[35][36][37][40][41][42], according to electrophoretic, chromatographic, and proteomic analysis. The properties of Micrurus venoms vary greatly among species, which is attributed to their diverse habitats and prey preferences as well as phylogenetic inertia [12,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…However, the venoms of the short-tailed triadal species M. helleri, as well as the two monadal short-tailed species M. medemi and M. sangilensis, are dominated by phospholipase components with PLA 2 comprising 40.6%, 43.1%, and 30.4% of the total venom proteins and 3FTx comprising 14.1%, 17.7%, and 17.7% of the total venom proteins, respectively. Similar results have been obtained for M. helleri from the Amazonian region of Colombia and Ecuador; in Colombia, PLA 2 and 3FTx comprise 62.5% and 21.1% of the total venom proteins, respectively, whereas in Ecuador, PLA 2 and 3FTx comprise 72.1% and 17.8% of the total venom proteins, respectively [36,37]. The proteomic composition of various coral snake species reported over the last four years, including this work, does not support the hypothesis of the divergent latitudinal pattern nor a triadal vs. monadal (or long-tailed vs. short-tailed) divergence for explaining the phospholipase/3FTx-dominant phenotypes (see Supplementary Table S1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Proteomic analyses of Colombian M. mipartitus venom revealed that its composition comprises three finger toxins (3FTx) (~60%) and phospholipase A 2 (PLA 2 ) (~30%), constituting the major components, followed by L-amino acid oxidase (4.0%), P-III metalloproteinase (1.6%), Kunitz-type protease inhibitor (1.9%), serine proteinase (1.3%), and C-type lectinlike families (1.1%) [31]. Costa Rican M. mipartitus also contains 1.9% KSPIs [31], while these proteins were not detected in M. mipartitus from Ecuador [43].…”
Section: Introductionmentioning
confidence: 98%